Tingkat Stres dan Perilaku Makan dan Status Gizi Selama Pandemi COVID-19: Tinjauan Pustaka - Rafkhani, Tesa; Mulyati, Rini (Media Gizi Kesmas, 2025)
Background: The COVID-19 crisis has heightened stress levels across the population, potentially triggering unhealthy dietary habits and contributing to weight gain. The stress experienced during this period is critical in shaping eating patterns and influencing nutritional health.  Objective: This study explores the existing literature on the connection between stress levels, dietary habits, and nutritional health among adults aged 18 to 65 during the COVID-19 pandemic.  Methods: A literature review examined articles from the PubMed-Medline and Google Scholar databases, focusing on publications from 2020 to 2022. The search terms included “Eating Behavior,” “Obesity,” “Mental Health” and, “COVID-19 Pandemic.”  Results: The COVID-19 pandemic led to increased emotional eating, decreased physical activity, and higher anxiety and depression, contributing to short-term weight gain and worsened obesity. Conclusion: The COVID-19 pandemic has had notable short-term effects on eating behaviors, mental health, and obesity risk. Interventions aimed at stress management and promoting healthy lifestyle habits during lockdowns are essential to mitigate adverse nutritional and psychological consequences.